Deleuze on cinema - Bogue, Ronald, 1948- (Deleuze and the arts ;, 2003)
This text provides a thorough and reliable guide to Deleuze's thought on the art of film, elucidating in clear language the shape and thrust of Deleuze's arguments found in his influential books on cinema.